Ischemic Stroke in a Young Adult: a Case Report - Lilibet Muñoa Garrido; Julio Michel Arias Manganelly; Yuliel Varona Rodríguez; Olenis Alicia Aldana Ramos (Revista Finlay)
Cerebrovascular disease has an incidence of 6 to 20 cases per 100,000 inhabitants annually, and it is estimated that up to 15 % occurs in the young population. Some reports have shown that it is more common in women between the ages of 20 and 30 and men over 35. We present the case of a 39-year-old patient with a history of smoking three packs of cigarettes a day who presented to the emergency department reporting that, in the morning, he suddenly began to speak incoherently and was disoriented. The initial physical examination, according to the Stroke Impact Scale, revealed a score of 8/42, dysarthria and disorientation, stable vital signs, and no sensory deficits. He was admitted with a diagnosis of atherothrombotic ischemic stroke of the posterior cerebral artery. Additional hematological, hemochemical, electrical, and imaging tests were indicated. The case is presented with the objective of describing the clinical manifestation of cerebrovascular disease in a young adult.